Effect of pasteurisation and foaming temperature on the physicochemical and foaming properties of nano-filtered mineral acid whey. (October 2022) - Purwanti, Nanik; Hogan, Sean A.; Maidannyk, Valentyn A.; Mulcahy, Shane; Murphy, Eoin G.
Abstract: Foaming can pose a major challenge during processing of acid whey (AW). In this study, nano-filtered mineral AW was collected from a commercial plant before (AW0 ) and after pasteurisation (AWpast ; 75 °C, 15 s). Both AW samples were foamed at 21 °C and in addition, AWpast was foamed at 61 °C, corresponding to the temperature of in-plant foaming. Physicochemical, foaming, and surface properties of AW samples were compared. Foaming at 21 °C resulted in less pronounced foam characteristics for AWpast compared with AW0 . Pasteurisation was found not to significantly affect physicochemical properties; however, interfacial kinetics during foaming were altered, which affected foaming behaviour. Foaming of AWpast at 61 °C produced more stable, "dry" foams. FTIR spectra confirmed the influence of protein unfolding at elevated temperatures on foaming, which was reversible upon cooling. This is significant as it gives processors a mean of controlling foaming through temperature control, where possible.